Hydatidosis Prevalence in 6- to 12-year-old Children in Southern Xinjiang - Zhao, Jiang-shan; Hou, Yan-yan; Zhang, Hai-ting; Ruziguli-Zhumahong (Zhongguo jishengchongxue yu jishengchongping zazhi, 2016)
To understand the hydatidosis prevalence in 6- to 12-year-old children in southern Xinjiang Uygur Autonomous Region and provide scientific basis for formulation of control measures. One primary school was selected from each of the pastoral area, pastoral-agricultural area, agricultural area, and township area in 42 counties （cities） of southern Xinjiang, using the stratified sampling method. With the consent of their parents, B ultrasonic abdominal scan and venous blood collection were performed on all the children （6-12 years） in the selected schools. Serum level of echinococcus antibody IgG was determined by ELISA. Hydatidosis prevalence and the serum level of IgG in these children were analyzed. A total of 80 429 children were examined from 168 primary schools. B ultrasonic scan revealed hydatidosis in 9 children （0.01%）, comprising 3 cases in Kezhou, 2 in Aksu, 2 in Bazhou, and 2 in Kashi. ELISA results showed that 4 189 children were positive for serum IgG, with a positive rate of 5.21%. The positive rat